Identification of a novel type IV pilus gene cluster required for gastrointestinal colonization of Citrobacter rodentium - Mundy, R; Pickard, D; Wilson, R; Simmons, C; Dougan, G; Frankel, G (Wiley, 2003)
Citrobacter rodentium is used as an in vivo model system for clinically significant enteric pathogens such as enterohaemorrhagic Escherichia coli (EHEC) and enteropathogenic E. coli (EPEC). These pathogens all colonize the lumen side of the host gastrointestinal tract via attaching and effacing (A/E) lesion formation. In order to identify genes required for the colonization of A/E-forming pathogens, a library of signature-tagged transposon mutants of C. rodentium was constructed and screened in mice. Of the 576 mutants tested, 14 were attenuated in their ability to colonize the descending colon. Of these, eight mapped to the locus of enterocyte effacement (LEE), which is required for the formation of A/E lesions, underlying the importance of this mechanism for pathogenesis. Another mutant, P5H2, was found to have a transposon insertion in an open reading frame that has strong similarity to type IV pilus nucleotide-binding proteins. The region flanking the transposon insertion was sequenced, identifying a cluster of 12 genes that encode the first described pilus of C. rodentium (named colonization factor Citrobacter, CFC). The proteins encoded by cfc genes have identity to proteins of the type IV COF pilus of enterotoxigenic E. coli (ETEC), the toxin co-regulated pilus of Vibrio cholerae and the bundle-forming pilus of EPEC. A non-polar mutation in cfcI, complementation of this strain with wild-type cfcI and complementation of strain P5H2 with wild-type cfcH confirmed that these genes are required for colonization of the gastrointestinal tract by C. rodentium. Thus, CFC provides a convenient model to study type IV pilus-mediated pathogen-host interactions under physiological conditions in the natural colonic environment.